2001
DOI: 10.1074/jbc.m007656200
|View full text |Cite
|
Sign up to set email alerts
|

Essential Tyrosine Residues for Interaction of the Non-receptor Protein-tyrosine Phosphatase PTP1B with N-cadherin

Abstract: Expression of a dominant-negative, catalytically inactive form of the nonreceptor protein-tyrosine phosphatase PTP1B in L-cells constitutively expressing N-cadherin results in loss of N-cadherin-mediated cell-cell adhesion. PTP1B interacts directly with the cytoplasmic domain of N-cadherin, and this association is regulated by phosphorylation of tyrosine residues in PTP1B. The following three tyrosine residues in PTP1B are potential substrates for tyrosine kinases: Tyr-66, Tyr-152, and Tyr-153. To determine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 31 publications
1
45
0
1
Order By: Relevance
“…PTP1B associates directly with the cytoplasmic domain of N-cadherin, as does the dominant-negative construct (Balsamo et al, 1996Rhee et al, 2001, Xu et al, 2002. We have recently determined the binding site on the cytoplasmic domain to which PTP1B is targeted (Xu et al, 2002).…”
Section: Maintaining Stable Adhesions: the Nonreceptor Tyrosine Kinasmentioning
confidence: 99%
See 1 more Smart Citation
“…PTP1B associates directly with the cytoplasmic domain of N-cadherin, as does the dominant-negative construct (Balsamo et al, 1996Rhee et al, 2001, Xu et al, 2002. We have recently determined the binding site on the cytoplasmic domain to which PTP1B is targeted (Xu et al, 2002).…”
Section: Maintaining Stable Adhesions: the Nonreceptor Tyrosine Kinasmentioning
confidence: 99%
“…Targeting is thus crucial for its proper functioning within cells. Interaction with Ncadherin depends on phosphorylation of tyrosine 152 in PTP1B (Rhee et al, 2001); alanine substitution of this residue abolishes the dominant-negative effect of the C215S mutant PTP1B and prevents localization at cell boundaries. Thus, an additional feature of this set of regulatory interactions is the potential to regulate the phosphorylation of PTP1B and, therefore, its association with cadherin and the content of phosphorylated tyrosine residues on ␤-catenin.…”
Section: Maintaining Stable Adhesions: the Nonreceptor Tyrosine Kinasmentioning
confidence: 99%
“…Similarly, in human breast carcinoma cells, E-cadherin inhibits EGFR activation via protein tyrosine phosphatase activation (55). EGFR and several protein tyrosine phosphatases reported to dephosphorylate EGFR (27,34,46,57) colocalize to E-cadherin-containing adherens junctions (1,47,58,65), suggesting that E-cadherin may modulate EGFR phosphotyrosine levels via recruitment of an EGFR-directed protein tyrosine phosphatase to adherens junctions. …”
mentioning
confidence: 99%
“…A role for PTP1B in the regulation of many cellular functions has been suggested, including integrin (20 -23), cadherin (24,25), and cytokine receptor signaling (26 -28), cell cycle regulation (29 -31), and the response to cellular stress (32). Multiple studies indicated that PTP1B dephosphorylates the EGFR (16,17) and the insulin receptor (IR) (14,(33)(34)(35).…”
mentioning
confidence: 99%